Perancangan Animasi Stopmotion Pangeran Diponegoro Berbasis Sinematografi - Sandi, Supriyadi (Jurnal Komunikasi, 2019)
Nowadays animated films are developing rapidly in Indonesia. Animated films are in demand because they are entertaining, but rarely found educative animated films that tell about history. In general, historical documentation is only based on thick textbooks, and the placement of photos of heroes on classroom walls is generally not interesting for students to enjoy. This encourages researchers to make an animated film that has historical and educational value. With appropriate cinematography, a film can have high artistic value. In addition, the film can also convey information and implied messages that can be used as lessons in life. To attract students, stopmotion technique was chosen. This stopmotion animation is created by applying the sine matography technique so that what will be conveyed in this animated film can be conveyed well to the audience. All of this aims to make the animation look livelier, smoother in its movements, and produce a more attractive appearance and is liked by the audience. It is better to make a stopmotion animation in a detailed storyboard design, so there are no mistakes when making motion, camera angles, type shots, and video translation. Stopmotion filmmaking is inseparable from photography and cinematography